2016
DOI: 10.1124/dmd.115.069187
|View full text |Cite
|
Sign up to set email alerts
|

KAE609 (Cipargamin), a New Spiroindolone Agent for the Treatment of Malaria: Evaluation of the Absorption, Distribution, Metabolism, and Excretion of a Single Oral 300-mg Dose of [14C]KAE609 in Healthy Male Subjects

Abstract: KAE609 [(19R,39S)-5,79-dichloro-69-fluoro-39-methyl-29,39,49,99-tetrahydrospiro[indoline-3,19-pyridol[3,4-b]indol]-2-one] is a potent, fast-acting, schizonticidal agent in clinical development for the treatment of malaria. This study investigated the absorption, distribution, metabolism, and excretion of KAE609 after oral administration of [ 14 C]KAE609 in healthy subjects. After oral administration to human subjects, KAE609 was the major radioactive component (approximately 76% of the total radioactivity in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…As parasite densities decline, the more slowly cleared sexual-stage parasites and any drug-refractory forms comprise an increasing proportion of the DNA signal. Recent ex vivo studies suggest that cipargamin does not induce the same refractory forms observed with artemisinin drugs ( 18 ), so the nature of the parasite forms, which persist despite exposure to high cipargamin concentrations, clearly requires further study ( 18 , 19 ). Low-dose primaquine was not given as a rapid gametocytocide in this study because cipargamin was considered to have gametocytocidal activity, but this was insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…As parasite densities decline, the more slowly cleared sexual-stage parasites and any drug-refractory forms comprise an increasing proportion of the DNA signal. Recent ex vivo studies suggest that cipargamin does not induce the same refractory forms observed with artemisinin drugs ( 18 ), so the nature of the parasite forms, which persist despite exposure to high cipargamin concentrations, clearly requires further study ( 18 , 19 ). Low-dose primaquine was not given as a rapid gametocytocide in this study because cipargamin was considered to have gametocytocidal activity, but this was insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…If parasites with a similar level of resistance to the in vitro selected parasites were to emerge in the field, it is likely that cipargamin would remain effective against them. In clinical trials, cipargamin has been found to reach supramicromolar concentrations in human plasma for sustained periods (28,(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously disclosed studies leading to the discovery of (+)-SJ733 (9), which has recently completed Phase 1 trials (10). (+)-SJ733 is the second inhibitor of PfATP4, a parasite proton-sodium antiporter, that has entered clinical trials -the other being cipargamin (11)(12)(13). We have shown that PfATP4 inhibitors selectively induce eryptosis of infected red blood cells leading to a rapid clearance of infected erythrocytes in vivo (9).…”
Section: Introductionmentioning
confidence: 99%